IDENTITY CRISIS THREATS YOUNG GENERATIONS IN INDONESIA - Elisha Samantha Dewi Manurung; Faukha Ilmania Salsabila; Putu Tanisya Putri Wirawan; Nadila Dwi Anggraini; Moses Glorino Rumambo Pandin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
In the life of the nation and the state, sometimes people feel confused about which is more important between the country and the state and sometimes even underestimate the two. The state is an organization of power from the fellowship of human life, while the nation refers more to the harmony of human life. A country must have its own national identity that differs from one country to another because the national identity of a nation shows its personality. This study aims to observe the condition of national identity for the young generation and efforts to overcome the threat of a national identity crisis. The method used is the descriptive analysis with data collection techniques through surveys and interviews. The population in this study were private high school and university students. In this study, the sample used was 160 people aged 15-20 years. The results found that the young generation is at a critical stage of national identity. It was caused by the inability to use technology wisely and a lack of sense of nationalism and love for the homeland. This study found many shortcomings, seen from the students still using their respective regional languages because they were vulnerable to triggers based on the perspectives, principles, and goals of each student. Furthermore, based on research results, teenagers tend to be more fond of foreign cultures and consider Indonesian cultural heritage outdated. For this reason, it is necessary to instill a sense of pride and love for the homeland for young people so that the culture remains sustainable. With this research, it is suggested that we care more about the national identity of the Indonesian nation to increase the horizon of knowledge, and it is also hoped that the Indonesian people, especially the young generation, can apply to understand related to national identity and be able to implement the points of Pancasila in life nation, society, and state.